BRAVE AND HARDWORKING: A FEMINIST ANALYSIS ON CHILDREN FAIRYTALE “THE LAZY GIRL” - Dewi Purnamasari; Didin Nuruddin Hidayat; Alek Alek (UIN Alauddin Makassar, 2020)
This study analyzed the feminist analysis of children fairytale